Length of Residence and Cardiovascular Health among Afro-Caribbean Immigrants in New York City - Thomas, Sabena C. (J Racial Ethn Health Disparities, 2018)
Cardiovascular disease (CVD) disproportionately affects non-Hispanic blacks (NHB) in the United States (U.S.). Afro-Caribbean (AC) immigrants comprise over 50% of the immigrant black population and are critical in understanding the health trajectories of blacks in the U.S. We assessed the relationship between length of residence (proxy measure for acculturation) and cardiovascular health (CVH) based on the American Heart Association’s (AHA) seven ideal cardiovascular health components among AC immigrants in New York City (NYC). CVH scores were categorized into poor/intermediate CVH (0–3 components) or ideal CVH (≥ 4 components). Multivariable logistic regression was used to examine the association between length of residence in the U.S. and poor/intermediate CVH. In adjusted models, the odds of poor/intermediate CVH were significantly higher for Guyanese (OR = 3.51; 95% CI 1.03–11.95) and Haitian immigrants (OR = 8.02; 95% CI 1.88–34.12) residing in the U.S. for ≥ 10 years than for those living in the U.S. for < 10 years. Length of residence was not significantly associated with CVH among Jamaican immigrants. We found evidence of ethnic differences in the association between acculturation and CVH among AC immigrants in a major metropolitan city. Culturally tailored interventions are needed to improve the CVH of AC immigrants as they become integrated into the U.S., with special consideration of country of birth.